Biological effectiveness of combined exposure to neutrons and gamma radiation applied in two orders of sequence: Relevance for biological dosimetry after nuclear emergencies - Tomas Palmqvist; Milagrosa Lopez-Riego; Martin Bucher; Ursula Oestreicher; Stefan Pojtinger; Ulrich Giesen; Iuliana Toma-Dasu; Andrzej Wojcik (Radiation Medicine and Protection)
Objective: To investigate the potential impact of two different combinations of neutron and gamma radiation on gene expression and dicentric chromosomes in peripheral blood mononuclear cells (PBMC). Methods: Whole blood from 3 human donors was exposed to neutrons with an energy spectrum similar to that of the Hiroshima uranium bomb, to gamma radiation from a 60Co source and to a 50:50 combination of both radiations, given in two orders of sequence. In all cases the total doses were 0.5, 0.75 and 1.0 ​Gy. Dicentric chromosomes were analyzed by light microscopy and the expression of six known radiation-responsive genes BBC3, CDKN1A, FDXR, GADD45A, MDM2, and XPC were analyzed by RT-qPCR. Results: Per unit dose, exposure to neutrons lead to a higher level of dicentrics and gene expression as compared to gamma radiation. Dose-response relationships for both endpoints were linear, allowing calculating the expected outcome of combined exposure by arithmetic. For dicentric chromosomes, the RBE values for 60Co → neutrons, neutrons → 60Co and neutrons were 4.05, 3.62 and 7.30, respectively. For gene expression the RBE values were gene-specific, but showed values in the range of 1.14–3.01 for 60Co → neutrons, 1.33–2.68 for neutrons → 60Co and 1.39–3.91 for neutrons. Conclusions: The results demonstrate that combined exposure to neutrons and gamma radiation, regardless of the order of sequence, leads to an additive response at both endpoints. This indicates that calibration curves for mixed beams can be constructed from dose response relationships of the single beam components.